Natural-Based Sustainable Filter Media for Ammonia and TSS Removal in Small-Scale Aquaculture - Pramudia, Zulkisam; Kurniawan, Andi; Anjasmara, Aang Setyawan; Anugerah, Putri; Moehammad, Khibar Syiar (Indonesian Green Technology Journal, 2025)
Water quality degradation gacorwin remains a critical challenge in small-scale aquaculture, particularly due to the accumulation of suspended solids and ammonia from feed waste and metabolic excretion. This study aimed to evaluate the efficiency of a simple, eco-friendly filtration system using natural materials—sand, zeolite, pumice, and coconut fiber—in removing Total Suspended Solids (TSS) and ammonia (NH?–N). Four treatments were tested over a five-day period: P1 (sand and zeolite), P2 (pumice and coconut fiber), P3 (all four materials), and a control (no filter media). Each unit was constructed using low-cost containers and operated under continuous flow conditions. Results showed that P3 consistently gacorwin achieved the highest removal efficiency, reducing TSS by 82.5% and ammonia by 83.3%. ANOVA and Tukey HSD tests confirmed significant differences (p < 0.05) among treatments. The combination of mechanical, chemical, and bioactive media in P3 enhanced both physical filtration and nitrogen removal. These findings support the application of natural-based filter media as a sustainable, low-cost solution for improving water quality in decentralized aquaculture systems, especially in resource-limited settings gacorwin